Association Between Sensory Impairment and Dementia in Older Adults: Evidence from China. Issue 3 (10th January 2018) - Luo, Yanan; He, Ping; Guo, Chao; Chen, Gong; Li, Ning; Zheng, Xiaoying
Abstract : Objectives: To determine the association between sensory impairment and dementia in Chinese older adults. Design: Cross‐sectional. Setting: Older adults in 31 provinces of China. Participants: Individuals aged 65 and older (N = 250, 752). Measurements: Psychiatrists ascertained dementia based on the International Classification of Diseases, 10th Revision . Sensory impairment was measured as only hearing impairment, only vision impairment, and combined sensory impairment (combined hearing and vision impairment). Hearing impairment was defined as greater than 40 dB loss in the better ear according to the standard of the World Health Organization (WHO) Prevention of Deafness and Hearing Impairment (PDH) standard 97.3. Ophthalmologists assessed vision impairment according to the WHO best‐corrected visual acuity (BCVA) criteria (low vision: 0.05≤BCVA ≤0.29; blindness: no light perception ≤ BCVA <0.05, visual field less than 10 degrees; the better‐seeing eye). Results: The prevalence of dementia was 0.41% (95% CI = 0.39–0.44%) without sensory impairment, 0.83% (95% CI = 0.70–0.99%) with only visual impairment, 0.61 (95% CI = 0.53–0.71%) with only hearing impairment, and 1.27% (95% CI = 1.00–1.61%) with combined sensory impairments. After adjusting for sociodemographic characteristics, vision impairment (odds ratio (OR) = 1.58, 95% CI = 1.28–1.96) and combined sensory impairments (OR = 1.64, 95% CI = 1.23–2.20) were associated with greater risk of severe to extremely severe dementia. Hearing impairment was not significantly associated with dementia. Conclusion: Sensory impairments are associated with greater risk of dementia in Chinese older adults. Studies are needed to further explore the pathway of this association in Chinese elderly adults and to provide suggestions to improve health status for this population.